Empowering MSMEs through Financial Literacy and Inclusion Drives Success in Indonesia: Memberdayakan UMKM melalui Literasi dan Inklusi Keuangan Mendorong Keberhasilan di Indonesia - Rizky, Muhammad; Fitriyah, Hadiah (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of financial literacy, financial inclusion, and the ability to prepare financial statements on the performance of MSMEs in Sidoarjo. Using a quantitative approach and multiple linear regression analysis with SPSS software, data were collected via questionnaires from 89 MSME owners in the food processing sector. The findings reveal that financial literacy and financial inclusion significantly enhance MSME performance, while the ability to prepare financial statements enables better financial control and decision-making. These results highlight the importance of improving financial skills and inclusion through targeted training and support programs to foster MSME growth. Highlight: Financial Literacy: Boosts MSME performance via better financial management and decisions. Financial Inclusion: Higher inclusion correlates with improved MSME outcomes. Financial Statements: Essential for financial control, identifying opportunities, and challenges. Keyword: MSMEs, financial literacy, financial inclusion, financial statements, performance